Seismic performance of framed underground structures with self-centering energy-dissipation column base. Issue 13 (October 2019) - Chen, Zhiyi; Zhou, Yu
For the development of underground structures toward large-scale, long-span, and complex structural styles, comprehensive seismic mitigation and controlling measures that consider reducing internal forces together with controlling lateral structural deformation and upgrading energy consumption are significant for improving seismic performance and enhancing resilience of underground structure. For this purpose, a self-centering energy-dissipation column base, which originated from the concept of earthquake resilient structures in aboveground space, is proposed for the framed underground structures in this study. To verify the effectiveness of self-centering energy-dissipation column base, three-dimensional time history analyses are conducted on a single-story double-span subway station. The analysis results show that the self-centering energy-dissipation column base effectively decreases the internal forces of central column and the peak and residual values of story drift and column drift are also minimized about 4%–5%. Meanwhile, it is found that a cyclic opening–closing exists at the column base during an earthquake and the uplift of column returns to zero at the end of the earthquake. It means the self-centering effect of the column base is achieved as expected. Moreover, replaceable energy-dissipating devices provide supplementary energy dissipation to relieve the development of structural plasticity and the uplift behavior of column base avoids the occurrence of plastic hinge. As a result, the structural damages are effectively reduced after the earthquake.